PROFIL LAYANAN DOSEN PEMBIMBING AKADEMIK - DEASY YUNIKA KHAIRUN; IBRAHIM AL HAKIM (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
The aim of this research is to profile the service of Academic Advisory provides guidance for students. Research also aim to found the barriers or obstacles encountered academic adviser in providing academic guidance services. This research use quantitative approach with questionare of Academic Advisory Service, interview the students and Academic Advisory Service, observation, and documentary study. Sample in this research are students of Guidance and Counseling Program Study and lecture who have the task as Academic Advisory in Guidance and Counseling Program Study. This research found that the Academic Advisory has giving all indicator service based on Statuta of Sultan Ageng Tirtayasa University and Standar Operational Procedur Academic Advisory Service. But, there are seceral obstacles or constraints faced by the Advisory Academid in the service of student guidance, such as time limitation od Advisory Academic, imbalance in the ratio between the number of Advisory Academid and discipline of students in following the schedule of academic guidance.